Exploring the nonlinear coded superposed modulation MISO visible light communication system - Zengyi XU; Wenqing NIU; Hui CHEN; Zhixue HE; Nan CHI (物联网学报)
The light-emitting diode (LED) based visible light multi-input single-output (MISO) system usually suffers from the nonlinearity in LED and its incoherent nature in emission.Adopting precoding would alleviate this limitation at comparatively lower cost.Existing researches usually apply the same coding scheme to all the channels.An asymmetric coding scheme was proposed, which nonlinearly encodes one of the two channels in a MISO system.This solution enlarges the dynamic range of the uncoded channel at the cost of a higher bit error ratio (BER) in the coded one.When the BER threshold is set at 3.8×10-3, the uncoded channel gains a dynamic range 30% larger than that of the coded one.If this solution is combined with flexible forward error correction redundancy, it would allow the system to adapt to varying channel condition while still maintaining the communication in both channels.This research would be beneficial in the study on indoor or underwater visible light communication (VLC) system.